EKSPLORASI MIKORIZA ARBUSKULAR PADA BEBERAPA SISTEM PENGGUNAAN LAHAN PERTANIAN DI DESA NGAWONGGO, KECAMATAN TAJINAN, KABUPATEN MALANG - Wikan Agung Nugroho; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Various crop commodities are grown in Ngawonggo Village with various land uses, including rice fields, dry fields and agroforestry which are dominated by intensive agriculture. As a result, this agricultural pattern can potentially cause land degradation. One of the technological inputs in improving sustainable crop production systems is the application of mycorrhizal biofertilizers. This study aims to determine the level of population, mycorrhizal colonies and types of spores and the factors that influence them in rice fields with rice (Oryza sativa), dry fields with sengon (Paraserianthes falcataria), and agroforestry with coffee (Coffea sp.) and Durian ( Durio zibethinus). The study used a randomized block design with sampling on three land uses, with 5. The results obtained only one type of mycorrhizal spore of Glomus sp. on all land uses. The highest number of spores was in agroforestry land use, as much as 102 g-1 soil, and the lowest was in rice fields, as much as 10 g-1 soil. Mycorrhizal colonies on plant roots were the highest in agroforestry land use, it was found that 42.77% of coffee roots were colonized by mycorrhizae, followed by durian with a colonization proportion of 42.29%, rice fields with commodities had the lowest colonization proportion of 16.21%.